Coffered ceilings: posthumous plans and reconstruction. The Conception’s church (Los Realejos). - Marrero Alberto, Antonio (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
The discovery of the plans of the polychrome Mudéjar coffered ceilings of the Church of the Conception in Los Realejos (Tenerife), made with immediate after its loss in the fire of 1978, allow to raise, both its reconstruction in a reliable way and its study since a historical and structural perspective. The concern of its neighbors for the recovery of the church and its goods, as well as the almost complete reconstruction of one of the roofs, are the engine and result of a series of meetings and reclamations to reconstruct following like model to the original, which results antagonistic to the generalized way of proceeding in the Canary Islands, where the reedifications followed the fashions of the moment. An exemplary rebuilding is thus analyzed from a historicist perspective and absolutely true to the original building.